Urine Results as A Predictor of Acute Kidney Failure after Radical Cystectomy and Ureterocutia Stoma - Iwan, Iwan; Majid, Abdul; Fitriani, Lya (GLOBAL HEALTH SCIENCE GROUP, 2024)
Acute kidney failure (AKI) is a spectrum of diseases characterized by changes in urine production and serum creatinine concentration. In recent years the concept of kidney injury and failure has evolved, replacing the term